Synthesis of Palm Biodiesel Using Direct Application of Pure Sodium Methoxide as the Catalyst - Azhari, (2006)
Palm biodiesel (methyl ester) was successfully synthesized from refined bleached deodorized palm oil (RBDPO) by transesterification reaction. The alkali catalyst was selected for this reaction, and the effects of operating variables such as molar ratio, reaction temperature, reaction time, and quantity of catalyst were investigated. The reaction was carried out under atmospheric pressure. The reaction temperatures were varied among 55, 60, 65 and 70°C, while the reaction times were between 50, 60, 70, 80 and 90 min respectively. The effects of two alkali catalysts namely sodium methoxide (NaOCH3) and sodium hydroxide (NaOH) at catalyst amounts of 1.0% w/w and molar ratios of methanol to RBDPO at 3:1, 4:1, 5:1, and 6:1 were investigated on reaction yield. The optimum conditions for NaOCH3 catalyst are as follows: reaction temperature is 65°C, reaction time is 60 minutes, molar ratio is 6:1, and catalyst amount, 1.0% w/w. The reaction conversion was almost 99%. While using NaOH catalyst, the conversion was 94%. The low pour point palm biodiesel was produced through winterization and vacuum distillation process. The vacuum distillation operated under pressure and temperature were between 5.2-6.0 mbar and 156-158°C. Basically, the lower the content of saturated components in a biodiesel, a better pour point biodiesel would be produced. However, in this experiment, the lowest of saturated component achievable was 16% w/w, and the lowest pour point attainable for palm biodiesel was at 3°C. Besides that, the kinetics study on transesterification of RBDPO with methanol established that the reaction occurred via two stepwise and irreversible elementary reactions. The rate constants for the formation of intermediate diglycerides and the final product palm oil methyl esters were determined at various temperatures. The conversion of triglycerides (TG) and diglycerides (DG) appeared to be following the second order reaction. The values of kTG were between 0.005 – 0.013 and the values of kDG were between 0.019 – 0.027. The activation energies for stepwise reaction in transesterification of palm based oils with methanol ranged from 6.87 to 11.45 kcal/mol.